Immune characteristics and SALL1 methylation as prognostic biomarkers in primary and metastasis colorectal cancer - Yiwen Zhang; Tianqi Han; Hui Zhang; Jiali Li; Jun Chu; Jiaqi Liu (Scientific Reports)
Abstract Colorectal cancer (CRC) and its metastatic form (mCRC) demonstrate considerable biological and clinical heterogeneity. By analyzing transcriptomic data from CRC and mCRC patients, we identified significant differences in gene expression profiles between the two. Our study focused on immune-related differentially expressed genes, which enabled the classification of CRC patients into four distinct subgroups based on their gene expression patterns. These subgroups exhibited marked differences in overall survival (OS) and immune infiltration levels, with Group 1 characterized by a robust immune response.To refine prognostic assessment, we employed a LASSO regression model to select core genes and developed a risk scoring system with promising clinical utility. Furthermore, methylation analysis uncovered notable epigenetic distinctions between CRC and mCRC, particularly involving the SALL1 gene and its methylation sites. Among these, the methylation level at the cg13755795 site emerged as an independent prognostic biomarker, offering predictive value for patient outcomes.Our findings provide a comprehensive view of the transcriptomic and epigenetic differences between CRC and mCRC, identify novel prognostic biomarkers and therapeutic targets, and propose potential strategies for personalized prognosis prediction and targeted therapy. This work contributes valuable insights into immune regulatory mechanisms and supports the development of advanced treatment approaches for colorectal cancer.